Yearbook of the Maimonides Centre for Advanced Studies 2019 - Meyrav, Yoav (De Gruyter, 2021)
The Yearbook of the Maimonides Centre for Advanced Studies mirrors the annual activities of visiting fellows, staff, and affiliates of the Maimonides Centre of Advanced Studies—Jewish Scepticism, Universität Hamburg. Its main section contains scholarly articles about Judaism and scepticism, both individually and together, among different thinkers and within different areas of study. Each volume of the Yearbook also includes a section with an overview of the activities and events conducted at MCAS during a given academic year, as well as a report on its library.